Water conservation significance of municipal solid waste management: a case of Xiamen in China. (15th August 2016) - Huang, Chu-Long; Yu, Chang-Ping; Lin, Tao; Ye, Zhilong
Abstract: The increase of municipal solid waste (MSW) with urbanization is causing serious environmental problems as well as resource shortage. Thus, accounting virtual water content of MSW within a city could indicate resource-saving significance of waste management, and can further strengthen integrated policy-making on both resource use and waste management in urban metabolism contexts. However, virtual water saving efforts from recycling MSW are currently lacking in the literature. Therefore, to foster attention on this area, an evaluative framework for virtual water in MSW has been developed for systematic management of resource metabolism. Accumulated virtual water contained in MSW from Xiamen for 2004, 2008 and 2012 was evaluated by process analysis, based on statistical and survey data of MSW. Following the evaluation, we found that efficient management of MSW would improve its recyclability and promote virtual water saving, as observed from the virtual water saving potential of MSW during recycling, which range from 483.9 to 7633.3 m 3  tonne −1 . Likewise, the total virtual water amount in MSW in Xiamen rapidly increased from 2004 to 2012, total virtual water amount in MSW in Xiamen in 2004 is 2757.9～36750.4×10 5 m 3, total virtual water amount in MSW is 7574.4～68957.2×10 5 m 3 in Xiamen in 2012, as per capita MSW collection went up from 2002 to 2013 slowly. Therefore, encouraging source separation collection of MSW is necessary in relation to decisions regarding sustainable management of MSW and water resources, verified by evidence that per tonne of wastepapers, woods/bamboos, and food remnants contain much higher virtual water than that of other MSW components. Furthermore, integrated water management through production processes of MSW's components has proved important for saving water resources and improving environmental performance, due to the higher water consumption during planting, farming, or growing of raw materials than other processes of production. This is verified by the annual virtual water contained in food remnants, which account for more than 85% of total virtual water discharged with MSW in the selected years, with fish and shrimp taking the dominant part of virtual water content of food remnants. Certainly, MSW recycling would play great role in improving urban water metabolism efficiency as revealed by findings from this study. Hence, accounting for virtual water content of MSW could expand virtual water research field from product trade to MSW management. Graphical abstract: Highlights: MSW recycling would enhance the capacity of water resources supporting urbanization. Virtual water accounting of MSW in Xiamen was conducted by components and processes. The water saving potential of MSW recycling is huge and increasing in Xiamen. MSW source separation collection is critical for sustainable water use. The accounting provides systematic data for integrated management of water and waste.